ARTERIAL SUPPLY OF THE PELVIC LIMB OF THE ALPACA (VICUGNA PACOS) - Angulo A., José (2013)
The aim of this work was to identify and describe the arterial vessels of the pelvic member of the alpaca (Vicugna pacos). Six adult alpacas were dissected (3 females and 3 males). There were no anatomical differences between males and females. The arterial blood supply leading to the pelvic limbs mainly originates from the external iliac artery and to a lesser extent from the internal iliac artery, as described also for the canine, equine, bovine and llama. The external iliac artery is the main arterial channel that runs through the different regions of the pelvic limb, changing the name (femoral, popliteal, cranial tibial, dorsal pedal), giving off several collateral branches during its course. The superficial circumflex iliac, lateral circumflex femoral, saphenous, the proximal and distal caudal femoral arteries arose from the femoral artery as does the medial circumflex femoral artery. In the alpaca, coinciding with the llama, did not present the deep femoral artery as described in other domestic animals such as dog, horse and bovine. The popliteal artery gives off to the descending genicular artery, as the first collateral branch, the sural arteries and other branches that were distributed at the knee. The longer cranial tibial artery and the less developed caudal tibial have a distribution very similar to that described in the llama. At the level of the tarsus, the saphenous artery divides into the lateral plantar and medial plantar arteries. In the hindfoot, the medial plantar artery has a greater anatomical presence, being its contribution vital to the digital blood perfusion, as occurs in the llama. Thus, although in the pelvic limb of the alpaca has been observed several homologous arteries described in the classic texts of anatomy of domestic animals, they mostly followed an arterial pattern similar to that of the llama.